Allium sativum: A potential natural compound for NAFLD prevention and treatment - Mardi, Parham; Kargar, Reza; Fazeli, Ramina; Qorbani, Mostafa (Frontiers in Nutrition, 2023)
Introduction: Non-alcoholic fatty liver disease (NAFLD) results from an excessive accumulation of fat particles that causes liver inflammation, which ultimately causes liver damage. There is still considerable uncertainty about the effects of any nutritional supplements compared to no additional intervention. This review aimed to evaluate the efficacy of Allium sativum (A. sativum), known as garlic, in preventing and treating NAFLD. Methods: A systematic search based on a search strategy consisting of two components of "NAFLD" and "Allium sativum" in databases including PubMed, Web of Science (WoS), and SCOPUS was conducted on papers evaluating the effects of A. sativum on NAFLD treatment and prevention. We obtained studies from inception until September 20, 2022, followed by study selection and data extraction based on our eligibility criteria. Consequently, qualitative and quantitative synthesis was conducted. Results: Our qualitative analysis reveals that A. sativum consumption is linked to the prevention of NAFLD, especially in males, although qualitative data in this study regarding the therapeutic properties of NAFLD was controversial. Our meta-analysis showed that NAFLD patients treated with A. sativum have significantly declined aminotransferase levels. That is to say, our meta-analysis revealed a lower alanine transaminase (ALT) (SMD=-0.580, 95%CI=-0.822 to -0.338), and aspartate transaminase (AST(SMD=-0.526, 95%CI=-0.767 to -0.284) in NAFLD patients treated with A. sativum compared to the placebo group. Also, pooling data from case-control studies showed that A. sativum consumption decreases the odds of being diagnosed with NAFLD by 46% (OR= 0.538, 95%CI= 0.451 to 0.625). Conclusion: A. sativum consumption is not merely associated with NAFLD prevention but also results in a considerable decline in blood aminotransferase levels in patients diagnosed with NAFLD. To put it simply, A. sativum is linked to a decline in AST and ALT, which are considered reliable biomarkers of NAFLD response to treatment. Nevertheless, A. sativum is insufficient to improve NAFLD independent of other dietary amendments and lifestyle modifications.